The Problem of Oligopoly: A Comment - Davies, J. H. (Review of Economic Studies, 1954)
Journal Article The Problem of Oligopoly: A Comment Get access J. H. Davies J. H. Davies Sheffield Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 22, Issue 3, 1954, Pages 228–229, https://doi.org/10.2307/2295881 Published: 01 January 1954